2021
DOI: 10.1016/j.celrep.2021.108952
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial biogenesis in developing astrocytes regulates astrocyte maturation and synapse formation

Abstract: The mechanisms controlling the post-natal maturation of astrocytes play a crucial role in ensuring correct synaptogenesis. We show that mitochondrial biogenesis in developing astrocytes is necessary for coordinating post-natal astrocyte maturation and synaptogenesis. The astrocytic mitochondrial biogenesis depends on the transient upregulation of metabolic regulator peroxisome proliferator-activated receptor gamma (PPARg) co-activator 1a (PGC-1a), which is controlled by metabotropic glutamate receptor 5 (mGluR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 104 publications
0
58
0
Order By: Relevance
“…In previous studies, indications of the association between mGluR5 and mitochondrial function have been found. MGluR5 was shown to modulate ATP levels in different types of cells [74][75][76], production of ROS [15,72,75,77], mitochondrial mass [75] and mitochondrial biogenesis [78]. Our study revealed that mGluR5, in addition to these, can also regulate specific mitochondrial proteins, morphology and NADP/H level.…”
Section: Discussionmentioning
confidence: 58%
“…In previous studies, indications of the association between mGluR5 and mitochondrial function have been found. MGluR5 was shown to modulate ATP levels in different types of cells [74][75][76], production of ROS [15,72,75,77], mitochondrial mass [75] and mitochondrial biogenesis [78]. Our study revealed that mGluR5, in addition to these, can also regulate specific mitochondrial proteins, morphology and NADP/H level.…”
Section: Discussionmentioning
confidence: 58%
“…Of note, this temporal relationship indicates other mechanisms may exist. Zehnder et al (2021) discovered that there is a transient high expression of astrocytic mito oxidative metabolism relevant genes, such as mitochondrial biogenesis genes (PGC-1α and PGC-1β), and oxidative phosphorylation genes (Cox5b, Cox41l, Atp5a1, and Cycs) during the third week following birth. Accordingly, astrocytes contain more ATP content and consume more oxygen during the third post-natal week compared to day 50.…”
Section: Astrocyte As a Component Of The Whole Synapsementioning
confidence: 99%
“…The regulation of the mitochondrial network in the processes of astrocytes is associated with the differentiation and maturation of astrocytes, their participation in the maintenance of synapses, and the glial response to damage [70]. The importance of the functioning and morphogenesis of astrocytes was shown for several proteins involved in mitochondrial biogenesis and mitophagy, including peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1a) [71], autophagy-related proteins ATG7 [69] and ATG5 [72], and p62 [73].…”
Section: Mitophagy In Glial Cells In Aging and Neurodegenerationmentioning
confidence: 99%